Estudio de puestos de trabajo en el área administrativa del Gobierno Autónomo Descentralizado de Mejía - Canchig Cevallos, Nancy Verónica (2017)
The present research project consists of a study of jobs in the administrative area of the Autonomous Government decentralized of Mejía, a municipal entity whose main activity is the public administration, the satisfaction of the needs of citizens and the quality of its service to community. It will begin with a description of the activities performed in each job, identifying the existence of high risk groups due to exposure to repetitive movements and bad postures that cause musculo-skeletal discomfort, injuries and morbidity. It will take as reference the descriptive and field method based on facts of the investigative contribution, the collection of data within the work environment through the use of the analysis of job by task, the observation, check list and INSHT matrix will be able to identify the activities with greater possibility of damage to the health of the people who work in the institution, once the identification is made, the assessment of occupational hazards is carried out in the best case to avoid absenteeism in the work areas. Precautionary measures are proposed to control the risks in addition to a proper occupational health surveillance by providing employees with the information necessary to prevent accidents, improve their quality of life, optimize their performance in a comfortable and safe environment, Making active pauses in this way is intended that the work site is in line with the activities carry out achieving the labor satisfaction and increased productivity.